2011
DOI: 10.1089/acm.2010.0135
|View full text |Cite
|
Sign up to set email alerts
|

Relaxing on a Bed of Nails: An Exploratory Study of the Effects on the Autonomic, Cardiovascular, and Respiratory Systems, and Saliva Cortisol

Abstract: Healthy participants habituated to the induced pain on the BN and were able to subjectively relax. When on a BN, signs of both sympathetic and parasympathetic nervous system activity were observed. The pain may hypothetically have triggered a parasympathetic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 10 publications
(8 reference statements)
0
29
1
Order By: Relevance
“…A recent study investigating the effect of a NSP in healthy young volunteers showed substantial effects on cardiac autonomic responses and reactions of the sympathetic and parasympathetic nervous system, such as self-rated relaxation, blood pressure, heart rate, heart rate variability, and back temperature [25]. In contrast to the data presented here, the pad was bigger in size and covered a larger area of the back.…”
Section: Introductioncontrasting
confidence: 65%
See 3 more Smart Citations
“…A recent study investigating the effect of a NSP in healthy young volunteers showed substantial effects on cardiac autonomic responses and reactions of the sympathetic and parasympathetic nervous system, such as self-rated relaxation, blood pressure, heart rate, heart rate variability, and back temperature [25]. In contrast to the data presented here, the pad was bigger in size and covered a larger area of the back.…”
Section: Introductioncontrasting
confidence: 65%
“…The NSP—with more than 1000 sharp, but nonpenetrating plastic needles, is usually placed on soft ground and the patient lies for a limited time period on top of the mat with the uncovered, painful part of the body. It is very popular in some countries (Scandinavia) and is distributed under numerous names [23–25]. Those devices all have in common that they contain a flexible material, mostly cloth or soft plastic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies addressed the impact of different sleep stages (Chouchou et al., ), different stages of the menstrual cycle (Tousignant‐Laflamme and Marchand, ), the degree of muscle sympathetic nerve activity (MSNA; Fazalbhoy et al., ) or baseline HRV (Appelhans and Luecken, ) on interindividual variability in pain sensitivity. Additionally, a group of studies investigated interventions to alter the pain experience such as placebo capsules (Aslaksen et al., ), breathing manipulations (Chalaye et al., ; Martin et al., ) or listening to a CD with relaxation instructions (Olsson and von Schéele, ), and used HRV to monitor the outcome or differential effects of the interventions.…”
Section: Resultsmentioning
confidence: 99%